Pendugaan Umur Simpan Pasta Cabai dengan Penambahan Natrium Benzoat Menggunakan Metode Akselerasi Arrhenius - Lestari, Sri; Yuniarti, Silvia; Mutmainah, Hijriah; Hadiatry, Maureen C.; Hidayah, Ismatul (Jurnal Keteknikan Pertanian, 2021)
Chili paste is a processed chili product that has a promising prospect. Marketing problems are closely related to product shelf life. A method is needed to estimate the shelf life of the chili paste that will be marketed. The purpose of this study was to determine the shelf life of chili paste using the Accelerated Shelf-Life Testing (ASLT) method with the Arrhenius approach. The study used 5 treatments of Natrium Benzoate concentration, namely 0 g / kg of material, 0.25 g / kg of material, 0.5 g / kg of material, 0.75 g / kg of material and 1 g / kg of material. Storage was carried out at temperatures of 20 oC, 25 oC and 40 oC. Observations were made on days 0, 4, 8, 12 and 15. The critical parameter used was the panelist's preference value. 10 panelists were used to rate each sample of chili paste with a score of 1 to 6 (1 = disliked very much, 2 = disliked it, 3 = slightly disliked it, 4 = liked it a little, 5 = liked it, 6 = liked it very much). The results showed that the estimated shelf life of chili paste in the chili paste sample which was added with Natrium Benzoate was 0 g / kg of material, 0.25 g / kg of material, 0.5 g / kg of material, 0.75 g / kg of material and 1 g / kg of material at 25 oC, namely 3.37, 12.63, 12.93, 14.75 and 63.30 days respectively. The use of Natrium Benzoate as much as 1 g / kg of material is the maximum dose permitted in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 722 / MENKES / Per / IX / 1988.